Proceedings of the 8th Nordic Conference on Human-Computer Interaction: Fun, Fast, Foundational 2014
DOI: 10.1145/2639189.2639237
|View full text |Cite
|
Sign up to set email alerts
|

Thaddeus

Abstract: This paper introduces Thaddeus-a mobile phone-tablet system for mobile interaction with information visualisations. Our work is motivated by the roles smartphones and tablets play in everyday interactive spaces as well as anticipated developments in mobile sensing technology. We also aim to meet the social challenges of a data-driven society. We designed and implemented a system that uses mutual spatial awareness as an input mode, producing new interaction patterns for mobile settings. We gathered extensive us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…A first category of techniques focuses on 2D movement on a flat surface. Techniques include rotating devices to interact with content [143,270,288], moving devices to explore spatially aware maps [90,270], or to explore information visualisations [367]. The second category focuses on advanced 3D motions with devices for content interaction.…”
Section: On-screen | Touch Around Device | Gestures Device Motion 2d mentioning
confidence: 99%
See 1 more Smart Citation
“…A first category of techniques focuses on 2D movement on a flat surface. Techniques include rotating devices to interact with content [143,270,288], moving devices to explore spatially aware maps [90,270], or to explore information visualisations [367]. The second category focuses on advanced 3D motions with devices for content interaction.…”
Section: On-screen | Touch Around Device | Gestures Device Motion 2d mentioning
confidence: 99%
“…Both Informative → observational studies (e.g. interviews, diary study) [40-42, 75, 112, 148, 153, 252, 290] → gesture elicitation studies [166,230,271,305] Usage 219→ qualitative lab study [31,32,49,116,133,143,230,231,263,357] → quantitative user study [8,16,28,97,109,122,136,165,187,189,198,212,249,271,274,314,352,366] → mixed method lab study [7,54,190,191,206,255,264,302,352,367] → deployment in → social setting, conference [224,317,335] → classroom, students [37,53,…”
Section: Explicit Linking Between Devicesmentioning
confidence: 99%
“…Basés sur l'utilisation d'un smartphone comme dispositif complémentaire, de nombreux travaux se sont focalisés sur les intérêts que peut apporter leur combinaison avec une tablette. Dans Thaddeus [36], une représentation graphique de données peut être explorée à l'aide d'un smartphone en manipulant sa position relativement à la tablette. Dans BATMAN [24], la position du smartphone est utilisée pour déclencher des actions spécifiques dans une application comme la sélection d'un élément dans un menu circulaire ou la configuration de la taille du pinceau dans une application de dessin.…”
Section: Interaction Multi-dispositif Pour Tabletteunclassified
“…Goyal et al [14] showed how implicit sharing can help users in sensemaking over a distance using a desktop interface. RAMPARTS [42] illustrated how mobile devices allowed for more effective sensemaking than a tabletop interface and Thaddeus [43] showed that effective interaction with information visualisation on tablets was possible. On the other hand, Mayer et al [26] observed that mobile devices can also disrupt discussions.…”
Section: Data Exploration On Lhrds and Tabletsmentioning
confidence: 99%